Financial Communication of Global Commodity Price Information and Indonesian Stock Market Dynamics - Albet Rio Wijaya; Alni Rahmawati (INJECT (Interdisciplinary Journal of Communication), 2026)
Financial communication plays an important role in conveying global economic information that influences investor perceptions and market behavior. Among the most prominent forms of financial information are changes in global commodity prices, particularly oil and gold prices, which serve as information signals for investment decision-making. This study examines the relationship between global commodity price information and Indonesian stock market dynamics using the Autoregressive Distributed Lag (ARDL) approach. Annual data covering the period 1990–2025 were employed to investigate both long-run and short-run relationships among oil prices, gold prices, and the Indonesian stock market. The Augmented Dickey-Fuller (ADF) test indicates that all variables are integrated of order one, while the Bounds Test confirms the existence of a long-run equilibrium relationship. The long-run estimation results reveal that oil price information has a positive and statistically significant effect on stock market dynamics, whereas gold price information has a negative but statistically insignificant effect. In the short run, contemporaneous changes in gold prices do not significantly affect stock market performance, while lagged changes in gold prices have a positive and significant effect. The error correction term is negative and statistically significant, indicating a rapid adjustment toward long-run equilibrium following short-run disturbances. These findings suggest that investors respond differently to commodity-based information signals depending on the type and timing of information received. This study contributes to the interdisciplinary field of financial communication by highlighting how global commodity price information is reflected in stock market dynamics and investor responses.